(untitled) (ACME, 2023)
This paper aims to retrace some of the thematic correspondences between the De Aucupio by the Renaissance poet Pietro degli Angeli da Barga, otherwise known as ‘Bargeo’ (1517-1596), and the paraphrase of Dionysius’ Ixeutica (3rd-5th century CE), probably familiar to the poet thanks to the mediation of Conrad Gessner. After an overview of the protagonists, the paper will focus on an exemplary case from the De Aucupio, accompanied by a critical apparatus, and on the possible sources used by Bargeo.